Assistance for Villagers of Hanjeli Ciletuh Tourism Village, Palabuhanratu Geopark Sukabumi in Developing Hanjeli-Based Personal Care Products (Universitas Pendidikan Indonesia, 2023)
The development of new products made from hanjeli is one of the hopes of the residents of Waluran Mandiri Village to have superior products that are more diverse and able to increase tourist attraction. Non-food products for personal care groups such as bath soap or body lotion made from hanjeli which can be produced in a home made manner have the potential to be developed in Waluran Mandiri Village, but due to the limited knowledge and skills of community members who generally work as farmers, assistance through training in making personal care products is needed . Therefore this community service activity is carried out to organize training on making personal care products for the people of Waluran Mandiri Village. The activity consists of three stages, namely preparation of training materials, socialization of the training program and implementation of the training. The training material preparation stage consisted of product formulation trials, mockup product preparation, tutorial video creation, and pamphlet production which was carried out in the laboratory of the Indonesian Education University's Agro-industry Technology Education Study Program. Socialization of the training program is carried out through Rumah Hanjeli Indonesia. The training was held on June 29 2022 which was attended by five students of MTs Nurul Hidayah from Waluran Mandiri Village and seven activist residents of the Hanjeli tourism village. The personal care products that were trained on the participants were solid soap and Hanjeli body lotion. After the training, residents were able to mass produce hanjeli solid soap which was ready to be sold to the community. However, residents still need further assistance to produce their own hanjeli body lotion because the practice of making it is considered quite difficult. Therefore, further assistance is still needed for making hanjeli body lotion.